Hot Spots for Cold Fish: Geo-Heat Center Participates in Aquaculture Research - Rafferty, Kevin (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 1991)
The Geo-Heat Center is participating in a project to evaluate the performance of thermal refuge areas for over wintering of cold intolerant fish in outdoor aquaculture ponds. The project, under the direction of Dr. William Neill of Texas A&M University, will be undertaken at Redfish Unlimited in Palacios, Texas. Redfish Unlimited, managed by David Maus, is a commercial facility for culturing the popular food fish red drum (Scenops ocellatus), also known as redfish around the Gulf of Mexico